Corporate Governance in China: Shareholder Primacy under the Chinese Communist Party’s Influence - Zeng, Jie (Journal of Law and Commerce, 2025)
China, as a nominally socialist country, has a shareholder-primacy corporate governance model. Chinese company law grants shareholders strong rights, and Chinese companies have concentrated shareholding structures. As a result, shareholders can effectively dominate the board of directors and control the company. However, Chinese shareholders and companies are ultimately subject to the influence of the Chinese Communist Party (CCP). By drawing on empirical data, this article argues that Chinese corporate governance is sui generis. Shareholder primacy and party influence merge in a party-centered governance model in SOEs with party organizations (the CCP’s grassroots branches) dominating major decision-making. In private companies, shareholder primacy is the norm, and stakeholders are vulnerable to management’s exploitation and opportunism. The CCP sometimes intervenes to protect stakeholders but sometimes sides with companies. Its stance depends on its policy goals, which might vary from case to case and from time to time.